2015
DOI: 10.1007/s11764-014-0423-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life is associated with physical activity levels among colorectal cancer survivors: a longitudinal, 3-year study of the PROFILES registry

Abstract: Our results underline the importance to focus upon training in survivorship care and strategies to get inactive cancer survivors physically active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 25 publications
3
59
0
Order By: Relevance
“…In particular, some studies have found significant associations with social functioning, [32,33,36] while others did not. [39,43] In addition, most studies did not demonstrate an association with emotional functioning/mental health, [32,36,37,39,43] but one prospective study found an inter-individual effect of meeting MVPA guidelines with better emotional functioning [33] and two crosssectional studies reported a significant association of higher MVPA levels with lower distress [29] and lower anxiety symptoms. [42] These differences may be caused by differences across study populations (e.g., by age and time since diagnosis), or by differences in methods of assessing social and emotional functioning (which may be more subjective than physical functioning scales).…”
Section: Observational Studies Of Physical Activity and Quality Of Lifementioning
confidence: 98%
See 3 more Smart Citations
“…In particular, some studies have found significant associations with social functioning, [32,33,36] while others did not. [39,43] In addition, most studies did not demonstrate an association with emotional functioning/mental health, [32,36,37,39,43] but one prospective study found an inter-individual effect of meeting MVPA guidelines with better emotional functioning [33] and two crosssectional studies reported a significant association of higher MVPA levels with lower distress [29] and lower anxiety symptoms. [42] These differences may be caused by differences across study populations (e.g., by age and time since diagnosis), or by differences in methods of assessing social and emotional functioning (which may be more subjective than physical functioning scales).…”
Section: Observational Studies Of Physical Activity and Quality Of Lifementioning
confidence: 98%
“…[41] As physical activity guidelines around the world have typically focused on MVPA, most studies have examined time spent in MVPA per week, or adherence to MVPA guidelines (achieving 150 min/week; yes/no). [29,[32][33][34][35][36]38,39,[41][42][43] Some studies examined total physical activity (incorporating all intensities), [35,37] light physical activity [35,43] or specific types of physical activity (e.g., exercise [30,31,37] and/or recreational activities). [37,40] A variety of quality of life outcomes have been assessed across different studies, including overall/global quality of life (general health), [30][31][32][33][36][37][38][39][40][41]43] physical functioning, [29][30][31][32][33][35][36][37]39,43] role functioning, [32,33,36,43]…”
Section: Observational Studies Of Physical Activity and Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is associated with a higher risk of developing cancers, such as colon, esophageal, breast, renal, gallbladder, thyroid, and endometrial [119]. Physical activity has also been associated with a decreased risk of colon cancer and longer survival [120122]. The development of diabetes or pre-diabetes has also increased dramatically in China [123].…”
Section: Obesity—lack Of Physical Activitymentioning
confidence: 99%